Pengaruh Agen Sosialisasi dan Iklan TV terhadap Sikap dan Perilaku Menyikat Gigi pada Siswa Sekolah Dasar - Zikri, Zikri; Yuliati, Lilik Noor; Simanjuntak, Megawati (Jurnal Ilmu Keluarga dan Konsumen, 2019)
This study aims to analyze the influence of socialization from peers, family / parents, schools, and television advertisements on the attitude and behavior of brushing teeth. The study was conducted in two groups of fifth grade elementary school students in South Tangerang who had been exposed and who had not been exposed to a healthy school program selected using multistage sampling. The total number of respondents was 240 students from four different schools with each group consisting of 120 students from two schools selected using the quota sampling approach. Data was collected by self-reporting techniques and analyzed using descriptive analysis, different tests, and Structural Equation Modeling-Partial Least Square (SEM-PLS). The results showed a significant difference between the two groups of students on socialization variables from peers, family/parents, socialization of TV ads, attitudes, and brushing behavior. The results showed that in the group of students exposed to healthy school programs, attitudes were influenced by variables of socialization from family/parents and TV ads socialization. Attitudes didn’t have a significant effect on toothbrushing behavior. Child’s toothbrushing behavior was significantly influenced by socialization from school. Meanwhile, toothbrushing behavior in groups of students who had not been exposed to a healthy school program was influenced by the TV advertisements socialization.